Social media, consumer culture and sustainable lifestyles: Some evidence from a youth civil society group - Theodoridis Κonstantinos (Social Cohesion and Development, 2026)
Sustainability issues and sustainable lifestyles have been a crucial subject in the public sphere. There is a need to understand the ways social media narratives might affect consumer culture and behaviour in relation to sustainable consumption practices and fashion. By focusing on a civil society group of young people on Instagram, this paper seeks to understand how young volunteers communicate to their audience about consumerism, unsustainable lifestyles and the need to reconsider everyday consumption practices. In particular, it explores the role of social media in the ways young people support and advocate for a socio-environmental change. Through a literature review and a thematic analysis of the posts, it is demonstrated how social media can be used by youth groups in order to challenge unsustainable practices, educate consumers and promote alternative consumer lifestyles.